Transcutaneous auricular vagus nerve stimulation to treat narcolepsy type 1 (TARGET-NT1): A two-arm, randomised, sham-controlled trial - Yuanhang Pan; Yingchi Zhang; Ziliang Xu; Zihan Wei; Rui Pan; Gengyao Hu; Xiaoli Wang; Lei Yang; Dianwei Wu; Xinbo Zhang; Xinyu Wen; Shuyi Qu; et al. (Neurotherapeutics)
To assess exploratorily the safety and efficacy of transcutaneous auricular vagus nerve stimulation (tVNS) as an adjunctive therapy in improving symptoms in patients with narcolepsy type 1 (NT1). The TARGET-NT1 trial, a two-arm, double-blinded, sham-controlled trial was conducted from April 2022, to June 2024 ​at Xijing Hospital in Xi'an, China. Participants were randomised to receive tVNS treatment or sham tVNS (stVNS) treatment. Both interventions were performed for two 30-min periods per day with the same stimulation parameters but different stimulation points, for 12 weeks. The primary outcome was the change in mean sleep onset latency of maintenance of wakefulness test (MWT) from baseline to week 12. Secondary outcomes included changes in Narcolepsy Severity Scale (NSS), Epworth Sleepiness Scale (ESS), 14-item Hamilton Anxiety Rating Scale (HAMA-14), 17-item Hamilton Depression Rating Scale (HAMD-17). Among 60 randomised participants (32 men [53.3 ​%] and 28 [46.7 ​%]; mean [SD] age, 29.9 [9.9] years), 56 were included in the modified intention-to-treat (mITT) analysis. From baseline to week 12, the difference in mean change in mean sleep onset latency of MWT was 3.09 (95 ​% CI, 1.00, 5.88; P ​= ​0.0041) as compared with stVNS group. Significant improvements in NSS-EDS (−2.61 [95%CI, −4.07, −1.15; P ​= ​0.0006]), NSS-SP (−1.11 [95%CI, −1.83, −0.38; P ​= ​0.0030]), NSS-HH (−2.71 [95%CI, −3.36, −2.05; P ​< ​0.0001]), NSS- DNS (−0.52 [95%CI, −0.87, −0.17; P ​= ​0.0036]), ESS (−3.03 [95%CI, −4.30, −1.75; P ​< ​0.0001]) and HAMD-17 (−2.50 [95%CI, −4.30, −0.70; P ​= ​0.0069]) were observed in the tVNS group as compared with stVNS group. This exploratory study supported the efficacy and safety of tVNS in patients with NT1 and provided insights into the mechanisms underlying tVNS treatment for NT1. The findings highlight tVNS as a potential non-pharmacological adjunctive therapy for patients with NT1. This trial was registered with the Chinese Clinical Trial Registry, ChiCTR2400094550.